OPTIMIZATION OF OPERATION PARAMETERS OF 80-KEV ELECTRON GUN - JEONG DONG KIM; YONGDEOK LEE; HEUNG SIK KANG (Nuclear Engineering and Technology, 2014)
A Slowing Down Time Spectrometer (SDTS) system is a highly efficient technique for isotopic nuclear material content analysis. SDTS technology has been used to analyze spent nuclear fuel and the pyro-processing of spent fuel. SDTS requires an external neutron source to induce the isotopic fissile fission. A high intensity neutron source is required to ensure a high for a good fissile fission. The electron linear accelerator system was selected to generate proper source neutrons efficiently. As a first step, the electron generator of an 80-keV electron gun was manufactured. In order to produce the high beam power from electron linear accelerator, a proper beam current is required form the electron generator. In this study, the beam current was measured by evaluating the performance of the electron generator. The beam current was determined by five parameters: high voltage at the electron gun, cathode voltage, pulse width, pulse amplitude, and bias voltage at the grid. From the experimental results under optimal conditions, the high voltage was determined to be 80 kV, the pulse width was 500 ns, and the cathode voltage was from 4.2 V to 4.6 V. The beam current was measured as 1.9 A at maximum. These results satisfy the beam current required for the operation of an electron linear accelerator.